2020
DOI: 10.1155/2020/2434350
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Molecular Genetics of Methicillin-Resistant Staphylococcus aureus Colonization in Nursing Homes in Saudi Arabia

Abstract: Objective. Methicillin-resistant Staphylococcus aureus (MRSA) is one of the main causative agents of nosocomial infections that has posed a major threat to those with compromised immune systems such as nursing home residents. The aim of this study was to determine the rates of MRSA strains and the types of Staphylococcal Cassette Chromosome mec (SCCmec)in nursing homes in Saudi Arabia. Methods. A total of 188 nasal swabs were collected from the residents and nursing staff in two nursing homes in Riyadh, Saudi … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
3
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 27 publications
4
3
4
Order By: Relevance
“…The MDR isolates observed in the current study was 87/110 (79.1%) which is in line with a previous report in Ethiopia, 65(82.3%) (15). However, the MDR S. aureus observed in the present study is higher than a previous study reported from Ethiopia where 98(50.5%) of the S. aureus were MDR (17); in Eritrea, 17/43(39.5%) (18); and in Saudi Arabia where 47% of MRSA were MDR (23).…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The MDR isolates observed in the current study was 87/110 (79.1%) which is in line with a previous report in Ethiopia, 65(82.3%) (15). However, the MDR S. aureus observed in the present study is higher than a previous study reported from Ethiopia where 98(50.5%) of the S. aureus were MDR (17); in Eritrea, 17/43(39.5%) (18); and in Saudi Arabia where 47% of MRSA were MDR (23).…”
Section: Resultssupporting
confidence: 88%
“…As reported by Nwaogaraku et al from Nigeria showed that, all isolates of MRSA from blood samples of pigs were mecA negative on PCR (25). However, the present study is different from many studies done elsewhere (23,26,27). The possible explanation why phenotypically MRSA positive isolates did not show mecA gene might be due to loss of the mecA gene during prolonged storage (28) or other mechanisms other than the presence of mecA gene (mecC and mecB) responsible for methicillin resistant Staphylococcus aureus (29,30).…”
Section: Resultscontrasting
confidence: 87%
“…Nursing homes increase MRSA transmission and infection risk as a result of admission of elderly residents with premorbid conditions and weakened immune systems [ 37 39 ]. The MRSA colonization rate among residents in this study (24/496, 4.8%) was much lower than that in other studies showing 9.0% in Belgium [ 40 ], 9.04% in Saudi Arabia [ 41 ], and 14.5% in Crete; in Greece [ 12 ], the colonization rate we observed was slightly higher than that in Brazil (3.7%) [ 13 ] which may differ by geographic location.…”
Section: Discussioncontrasting
confidence: 90%
“…In the current study, out of 61 MRSA strains, SCCmecI and SCCmec V, SCCmecII , SCCmecIII, and SCCmecIV genes were detected in 16.3, 22.9, 36.3, and 21.3% of isolates. This finding was also reported by some researchers from South Africa [ 16 ], Saudi Arabia [ 17 ], and Venezuela [ 18 ]. Surprisingly, none of the MSSA strains carried the VF genes.…”
Section: Discussionsupporting
confidence: 87%